2022
DOI: 10.1002/jbio.202200272
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Feasibility of Raman spectroscopy as a potential in vivo tool to screen for pre‐diabetes and diabetes”

Abstract: This paper comments recent findings about Raman spectroscopy application for in vivo noninvasive diabetes detection, published in the Journal of Biophotonics by E. Guevara et al. (J. Biophotonics 2022, 15, e202200055). The proposed results may be not entirely correct due to possible overestimation of classification models and absence of additional information regarding age of tested volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Some recent papers [19] lack the description of the rule applied to selecting the optimal number of LVs or PCs (principal components) at all. In other manuscripts [20][21][22][23][24], the methodology of selecting the correct number of PCs/LVs raises doubts and leads to a significant overestimation of the classification models.…”
Section: Pls-da Analysis Of the Calibration Set And Cross-validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent papers [19] lack the description of the rule applied to selecting the optimal number of LVs or PCs (principal components) at all. In other manuscripts [20][21][22][23][24], the methodology of selecting the correct number of PCs/LVs raises doubts and leads to a significant overestimation of the classification models.…”
Section: Pls-da Analysis Of the Calibration Set And Cross-validationmentioning
confidence: 99%
“…Chemometrics methods have become widespread for RS data analysis, which is clearly reflected in a large number of manuscripts in the last few years [17,18]. However, several studies demonstrated the results that are characterized by significant overestimation of the proposed approaches based on the RS clinical effectiveness due to some flaws of applying the chemometric methods to analyze the RS data [17,[19][20][21][22][23][24][25]. In particular, using an unreasonably large number of principal components is the most common flaw in PLS that usually leads to overoptimistic results, for example, when a portable RS tool could provide the diagnostic result with an excellent accuracy [22,26].…”
Section: Introductionmentioning
confidence: 99%